Postcolonial churn and the impact of the criminal justice system on Aboriginal people in Western Australia, 1829–2020 - Roscoe, Katherine (Journal of criminology, 2022)
This article analyses how the criminalisation and imprisonment of Aboriginal people operated as tools of colonisation in Western Australia (WA) in the nineteenth century, and how this shaped the postcolonial criminal justice system. The racialised double standard embedded in the colonial foundations of state institutions, including the criminal justice system, rippled across generations of Aboriginal people: a reiterative and disruptive process that we dub the ?postcolonial churn?. This term, adapted from the ?carceral churn?, describes the destabilising mobilisations embedded in carceral and settler-colonial logics over the long term. It uses data from archival prison registers (Rottnest Island 1838?1931 and Roebourne Prison 1908?1961), as well as historic court, police and newspaper data to map the use of the criminal code in protecting and expanding colonial property rights in the original waves of settler-colonisation. WA is an outlier among the Australian colonies: it was the largest in terms of size (2,642,753 km2), the last colony to receive European convicts (1850?1868), and the last to be awarded self-government (1890). This created a situation where the British government dictated policy for legal forms of subjugation of Aboriginal people at the frontier (first for resisting pastoral industry, later as workers in it) which butted up against localised extra-legal violence by police and settlers. We can trace this dichotomy between policy and practice in the development of surveillance and policing of Aboriginal populations across time and settler-colonial space due to the protracted pace of frontier ?development?. Revealing the mediated historical aspects of structural racism is crucial to analysing the persistence of racialised policing in postcolonial settings and understanding why, despite repeated inquiries into mistreatment of Aboriginal people, institutional inertia remains.